The typology of second language listening constructs: A systematic review. (April 2023) - Aryadoust, Vahid; Luo, Lan
This study reviewed conceptualizations and operationalizations of second language (L2) listening constructs. A total of 157 peer-reviewed papers published in 19 journals in applied linguistics were coded for (1) publication year, author, source title, location, language, and reliability and (2) listening subskills, cognitive processes, attributes, and listening functions potentially measured or investigated. Only 39 publications (24.84%) provided theoretical definitions for listening constructs, 38 of which were general or had a narrow construct coverage. Listening functions such as discriminative, empathetic, and analytical listening were largely unattended to in construct conceptualization in the studies. In addition, we identified 24 subskills, 27 cognitive processes, and 54 listening attributes (total = 105) operationalized in the studies. We developed a multilayered framework to categorize these features. The subskills and cognitive processes were categorized into five principal groups each (10 groups total), while the attributes were divided into three main groups. This multicomponential framework will be useful in construct delineation and operationalization in L2 listening assessment and teaching. Finally, limitations of the extant research and future directions for research and development in L2 listening assessment are discussed.